The effects of Nigella sativa against oxidative injury in a rat model of subarachnoid hemorrhage - YEGEN, BERRAK; AKAKIN, DİLEK; ŞENER, GÖKSEL; YÜKSEL, MERAL (SPRINGER WIEN, 2011)
The aim of the study was to investigate the putative neuroprotective effect of Nigella sativa oil (NSO) treatment against subarachnoid hemorrhage (SAH) in rats. To induce SAH, rats were injected with 0.3 ml blood into their cisterna magna. Male Wistar albino rats were divided as control, vehicle-treated SAH, and NSO-treated (0.2 ml/kg, intraperitoneally) SAH groups. Forty-eight hours after SAH induction, neurological examination scores were recorded and the rats were decapitated. Brain tissue samples were taken for blood brain barrier permeability, brain water content, or determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO), and Na+-K+-ATPase activities. On the second day of SAH induction, neurological examination scores were increased in SAH groups, while SAH caused significant decreases in brain GSH content and Na+-K+-ATPase activity, which were accompanied with significant increases in MDA levels and MPO activity. The histological observation showed vasospasm of the basillary artery. On the other hand, NSO treatment markedly improved the neurological scores while all oxidant responses were prevented, implicating that NSO treatment may be of therapeutic use in preventing oxidative stress due to SAH.
Keywords: Subarachnoid hemorrhage; Nigella sativa; Oxidative stress; Cerebral ischemia; Cerebral vasospasm; ISCHEMIA-REPERFUSION INJURY; SPINAL-CORD-INJURY; ALPHA-LIPOIC ACID; CEREBRAL VASOSPASM; BRAIN-INJURY; MAJOR CONSTITUENT; IN-VITRO; THYMOQUINONE; DAMAGE; APOPTOSIS